The Ontological Nature of Part-Whole Oscillations: An Interdisciplinary Determination - STADLER, Michael (2020)
The nature of structures comprising part-whole relations belongs to the oldest, most fundamental and still discussed questions of philosophical ontology. Unlike many former approaches, which either give priority to the parts or to the whole of such structures, the present project is an ontological investigation that suggests an alternative to a hierarchical conception of parts and whole with a one-sided dependence relationship. In considering the dynamic 'in-between' or interplay of parts and whole, I develop and determine an ontological category called 'part-whole oscillations' (pwo).